Deamination of Betti bases: a facile route to 1-alkyl-2-naphthols and phenols via a metal-free transfer hydrogenation under microwave irradiation. Issue 27 (1st July 2015) - Dutta, Prantu; Pegu, Choitanya Dev; Deb, Mohit L.; Baruah, Pranjal K.
Graphical abstract